TESTICULAR ANATOMO-HISTOPATHOLOGICAL ALTERATIONSIN ALPACAS (VICUGNAPACOS) SLAUGHTERED IN NUÑOA, PUNO - Barrios S., William (2011)
The aim of the study was to determine the frequency and characterize testicularanatomo-histopathological alterations in alpacas slaughtered in Nuñoa, Puno.Macroscopic examination of the testes was carried out in 177 alpacas, which 102 showedsmaller size and low weight, and also uni or bilateral epididymal cysts. Tissue sampleswere fixed with the Bouin solution during 28 hours and stained with Haematoxylin andEosin, Periodic Acid Schiff and Masson’s Trichromic stain. The frequency of testicularalterations was 13.7%, corresponding to nonspecific lymphocytic infiltration (7.8%),testicular absence (2.9%), testicular degeneration (1.0%), hidrocele (1.0%), and teratoma(1.0%). Besides, there was 32.2% of epididymal cysts, but without statistical associationwith age or breed.